GENDER ANALYSIS IN MODERATING MOTIVATION AND INTENSIVITY TOWARDS GOJEK DRIVER PERFORMANCE - Cahyani Tunggal Sari; Yoga Nindita; Lukman Ahmad Imron Pahlawi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
In the midst of the condition of public transportation in Indonesia, especially in big cities in Indonesia, it has a poor level of service. This is reflected in the inconvenience and inconvenience of passengers when using public transportation as a result of overloaded public transportation, reckless drivers, prone to criminal acts, and many other indicators of the deterioration of public transportation services in Indonesia. Evidence of innovation in the ojek and taxi transportation business is the emergence of online ride-sharing operators by transforming online ojek and taxi services in Indonesia. This study aims to examine the factors that play a role in improving the performance of online drivers. The method used in solving problems using regression analysis. The results showed that the incentive variable had a positive and not significant effect on the performance of Gojek drivers, the motivation variable had a positive and significant effect on the performance of Gojek drivers, gender had a positive and not significant effect in moderating the incentive relationship with the performance of Gojek drivers, and gender had a negative and not significant effect on the performance of Gojek drivers. moderate the relationship between work motivation and the performance of Gojek drivers in Surakarta.